New perspectives on the development of extrahepatic portosystemic shunts - White, Robert N.; Shales, Chris; Parry, Andrew (Wiley, 2017)
Objective: To develop a hypothesis for the developmental modality of extrahepatic portosystemic shunts. Methods: A retrospective review of a series of dogs and cats managed for congenital portosystemic shunts. Using these data a hypothesis for the role of preferential venous blood flow in the development of common extrahepatic PSSs was postulated. In addition, an online literature search was used to retrieve peer-reviewed data describing the detailed anatomy of shunts in dogs and cats. A systematic review of these data was used as a preliminary test of the hypothesis. Results: In total 50 dogs and 10 cats met the inclusion criteria revealing five common and distinct shunt types. In the dog, these were spleno-caval, left gastro-phrenic, left gastro-azygos and those involving the right gastric vein. The online search confirmed that these were responsible for 94% of extrahepatic shunts described in this species. In the cat, the four shunt types observed were spleno-caval, left gastro-phrenic, left gastro-caval and left gastro-azygos. Excluding the left gastro-azygos, which from the online search was not described in the cat, the spleno-caval, left gastro-phrenic and left gastro-caval were responsible for 92% of extrahepatic shunts in this species. These data were used to develop, propose and provisionally test a hypothesis for the development of extrahepatic portosystemic shunts. Clinical Significance: We hypothesise that it is the presence of preferential blood flow that influences the subsequent formation of one of a number of defined and consistent congenital extrahepatic portosystemic shunts in dogs and cats.